Effective Family Parenting for the Child in the Face of Globalization - Antissar Sahraoui (The Journal of Studies in Language, Culture and Society)
Family is considered the first social institution where a child is raised. It is responsible for establishing solid and constructive foundations necessary for the child's adaptation and balance. The mother plays a crucial role in the educational function, followed by the father. This process is not easy, as it relies on skills that depend primarily on the nature of the parents' personalities and the quality of the relationship between them. Furthermore, the difficulty of the educational process is now linked to the manifestations of Western cultural globalization, which has penetrated all families. The widespread dissemination of communication tools has clearly impacted family cohesion and its function, leading to serious negative consequences that affect both the individual and society. This paper is an attempt to outline the most effective child-rearing methods, applicable to all families and societies, as they are derived from operational field studies based on scientific foundations.